Efficacy and safety of bupropion in cancer-related fatigue, a randomized double blind placebo controlled clinical trial - Ebrahim Salehifar; Saeid Azimi; Ghasem Janbabai; Ehsan Zaboli; Narjes Hendouei; Fatemeh Saghafi; Samaneh Borhani (BMC Cancer, 2020)
Abstract Background and objectives Cancer-related fatigue (CRF) is one of the most prevalent complications experienced by cancer patients during and after the process of treatment. Despite conducting a lot of studies, there is no approved therapy to help manage CRF. This study aims to investigate the efficacy of bupropion on CRF. Materials and methods In this double-blind randomized placebo-controlled clinical trial, a total of 30 eligible cancer patients suffering from fatigue were randomly divided into two groups (15 patients in each group). Bupropion was administered 75 mg/day for the first three days and 150 mg/day (divided in two doses) till the end of the study at week 6. Fatigue as the primary outcome was measured by BFI (Brief Fatigue Inventory) and FACIT-Fatigue (Functional Assessment of Chronic Illness Therapy) scales. Secondary outcomes included HADS (Hospital Anxiety and Depression Scale) and performance status (PS) measured by Karnofsky and ECOG (Eastern Cooperative Oncology Group) scales. Assessments were done at baseline, end of the second and sixth week. Results There was no significant difference between placebo and bupropion at baseline and the end of second week. Significant difference was seen between two groups at the end of week six (P = 0.006 based on BFI) in favor of bupropion. In-group assessment showed improvement in fatigue levels in both groups during study time (P = 0.000 based on BFI for both bupropion and placebo). Secondary outcomes (e.g., HADS and PS) were not different at baseline and the end of second week. However, at the end of week six, the difference was significant in favor of bupropion. Conclusion A six-week trial of bupropion reduces the CRF and improves the PS of cancer patients. Trial registration: Current Controlled Trials IRCT20090613002027N12, registration date: 2018-06-01.